1997
DOI: 10.1074/jbc.272.44.28133
|View full text |Cite
|
Sign up to set email alerts
|

Function of the R Domain in the Cystic Fibrosis Transmembrane Conductance Regulator Chloride Channel

Abstract: For a cystic fibrosis transmembrane conductance regulator (CFTR) channel to enter its open state, serine residues in the R domain must be phosphorylated by cAMP-dependent protein kinase, and intracellular ATP must bind to the nucleotide-binding folds and subsequently be hydrolyzed. CFTR with its R domain partially removed, ⌬R(708 -835)-CFTR, forms a chloride channel that opens independently of protein kinase A phosphorylation, with open probability approximately one-third that of the wild type CFTR channel. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
86
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 33 publications
7
86
0
Order By: Relevance
“…The Cterminal half of exon 13 appears to be the functional R ''regulatory'' domain (9,10). Consistent with this, deletion of residues 708-835 produces a CFTR channel with properties like those of wild-type CFTR, suggesting that residues 708-835 form a functional R domain that can be deleted (9,(12)(13)(14). More extensive deletions (residues 590-835, 656-835, 676-835, or 681-835) disrupted function (9), probably because they disrupt a portion of NBD1.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…The Cterminal half of exon 13 appears to be the functional R ''regulatory'' domain (9,10). Consistent with this, deletion of residues 708-835 produces a CFTR channel with properties like those of wild-type CFTR, suggesting that residues 708-835 form a functional R domain that can be deleted (9,(12)(13)(14). More extensive deletions (residues 590-835, 656-835, 676-835, or 681-835) disrupted function (9), probably because they disrupt a portion of NBD1.…”
mentioning
confidence: 55%
“…CFTR-⌬R͞S660A lacks the serines (660, 737, 795, and 813) shown to be responsible for the majority of PKA-stimulated channel activity (6,15,16,19). This channel differs from wild-type CFTR in two important ways: it has a low level of constitutive Cl Ϫ channel activity in the absence of PKA-dependent phosphorylation, and its activity is not altered by addition of PKA (9,(12)(13)(14).…”
mentioning
confidence: 99%
“…According to helical-wheel analysis, residues 733-739 and 761-777 (depending on the side chain conformation of Arg766) may also form amphipathic helices, and these might bind the same NBD1 surface as the regulatory extension, or other NBD1 surface(s), in a dynamic equilibrium. Additional residues of the R region, including 767-780, which interact with ATP-bound NBD1 independently of phosphorylation, may bind this same NBD1 surface or other NBD1 surface(s) 42 . Further NMR studies are currently in progress that focus on NBD1 to clarify the sites of R-region interactions.…”
Section: Two Predominant Mechanismsmentioning
confidence: 99%
“…PKA phosphorylation relieves this inhibition. On the other hand, it has been shown that exogenous phosphorylated R domain (either residues 590 -858, 645-834, or 708 -831) increases the open probability of a CFTR channel construct missing residues 708 -835 from the R domain (7,10,11).…”
mentioning
confidence: 99%
“…It is believed that the R domain combines both inhibitory and stimulatory effects. Effectively, deletion of the residues 708 -835 from the R domain (6,7), and even of the residues 760 -783 (8), generates constitutively active channels. Moreover, overexpression or addition of the unphosphorylated R domain, encompassing residues 590 -858, inhibits chloride transport (9).…”
mentioning
confidence: 99%